an efficient lot consensus algorithm based on rounds competitions - tei, ahmed; laouid, brahim (universty of elouedجامعة الوادي, 2021)
"تركز العديد من المهام الموثوقة على خوارزميات الإجماع التي تُستخدم لحل مشكلات الإتفاقية ولضمان موثوقية البيانات في شبكات (p2p) الغير الموثوق بها. في العديد من مجالات الشبكات ، يتم استخدام خوارزمية إجماع إثبات العمل(PoW) بشكل متكرر. ومع ذلك ، فإن آلية إثبات العمل النقية تعاني من ضعف استهلاك الطاقة الهائل وعرضة للهجوم بنسبة 51 ٪ . يختار هذا العمل التخفيف من عدم كفاءة الطاقة في خوارزمية الإجماع Blockchain Proof- of- Work (POW) من خلال إعادة تخصيص الطاقة التي يتم إنفاقها أثناء عملية التعدين بشكل عقلاني. تم تصميم مخطط تعدين PoW الأصلي للنظر في كتلة واحدة في كل مرة وتخصيص مكافأة للفائز بالمركز الأول في سباق الحساب. لتقليل استهلاك الطاقة المتعلقة بالتعدين ، نقترح تعويض الجهد الحسابي للعدائين (المتسابقين) في جولة التعدين ، من خلال منحهم التفرد في حل الكتلة القادمة في الجولة التالية (يقوم بعدة جولات من الثبات ). يجب أن تحل أي عقدة معينة لعبة الجولة 1 - N للمشاركة في الجولة N. علاوة على ذلك ، لا يمكن للعقد التي ستحل لعبة الجولة N أن تنتقل إلى الجولة التالية ، أي1 + N ، فقط عندما تكون محددة مسبقًا عدد الحلول التي تم حلها. سيؤدي هذا إلى ربح كبير من وقت االنتظار مع كل جولة بين العمليات المختلفة ، وبالتالي يمكن تحقيق توفير كبير في الطاقة يصل إلى 50٪. ""Several trusted tasks focus on consensus algorithms which are used to resolve agreement issues and to ensure the data reliability in untrusted P2P networks. In many networking fields, the Proof of Work (PoW) consensus algorithm is frequently used. However, the pure PoW mechanism suffers from the weakness of the huge power consumption and prone against the vulnerability of 51% attack. This work opts to mitigate the energy-inefficiency of the Blockchain Proof-of-Work (PoW) consensus algorithm by rationally repurposing the power spent during the mining process. The original PoW mining scheme is designed to consider one block at a time and assign a reward to the first place winner of a computation race. To reduce the mining-related energy consumption, we propose to compensate the computation effort of the runner(s)-up of a mining round, by granting them exclusivity of solving the upcoming block in the next round (he makes several rounds of proof). Any given node should resolve the game of the round N−1 to participate in the round N. Furthermore, the nodes that will resolve the game of the round N cannot pass to the next round, i.e., N+1 , only when a predetermined number of solutions has resolved. This will considerably Profit waiting time with each round between different operations, and consequently a significant energy saving up to 50% could thus be achieved."
mémoier master informatique
Keywords: إنترنت الأشياء ، خوارزمية الإجماع ، بلوك تشين ، نظير إلى نظير ، استهلاك الطاقة; IoT, Consensus Algorithm, Blockchain, Peer to Peer, Energy consumption